Comparative effectiveness of manual therapy and band exercises combined with high-intensity walking for pain, posture, and cardiorespiratory health in older adults: a randomised clinical trial - Arnal-Gómez, Anna; Fuentes-Aparicio, Laura; Marqués-Sulé, Elena; Monzani, Lucas; Cogollos-de-la-Peña, Rocío; Pavlu, Dagmar; Espí-López, Gemma Victoria (Frontiers in Medicine, 2025)
BackgroundMusculoskeletal pain and cardiovascular and pulmonary disorders affect the growing population of older adults. Manual therapy has proven to be effective, however, research using elastic bands is still scarce. The aim of this manuscript is to compare the effects of elastic band program training versus a manual therapy protocol, both combined with high-intensity walking, on age-related health parameters, such as pain, posture, and cardiorespiratory variables.MethodsA multicentre randomised clinical trial was conducted on community dwelling older adults with non-specific musculoskeletal pain. Participants were divided into two groups: (1) Manual therapy and high-intensity walking group (MTWG), who received self-assisted manual therapy followed by supervised high-intensity walking and (2) Elastic band and high-intensity walking group (EBWG) who performed resistance exercises with elastic bands and high-intensity walking. Musculoskeletal pressure pain threshold in trapezius muscles, back pain intensity, postural pattern (change in thorax position and chest wall expansion) and cardiorespiratory variables (heart rate and oxygen saturation, SpO2) were measured before the intervention (T0), after the 4-week programme (T1) and after the 4-week follow-up (T2).ResultsA total of 102 older adults (49 in the MTWG and 53 in EBWG) completed the study and were analysed. Five RM-MANCOVA models were specified. The EBWG showed significantly higher PPT scores than the MTWG across all data points (p < 0.01); a between-within-subjects effect was found for VAS scores (p < 0.05) (Model A). Statistically significant within-subject differences were found for the left acromion-to-bed distance scores (p < 0.05) but not for the right-side scores (Model B). Similarly, significant between-subject differences for the upper chest wall were found (p < 0.05), but not for the lower chest wall. However, univariate tests revealed significant within-subject for both the upper and lower chest wall scores. Finally, no significant differences were found in pulmonary function scores (Model D), heart rate (HR) or oxygen saturation scores (Model E).ConclusionBoth protocols reduce pain. Manual therapy helps with non-specific back pain and improves acromion-to-table posture, while elastic band treatment enhances trapezius pressure threshold and upper thoracic expansion. Neither improved lower thoracic mobility or respiratory variables.